2014
DOI: 10.1021/pr500558y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of GABA Transporters in Atropine-Treated Myopic Retina As Revealed by iTRAQ Quantitative Proteomics

Abstract: Atropine, a muscarinic antagonist, is known to inhibit myopia progression in several animal models and humans. However, the mode of action is not established yet. In this study, we compared quantitative iTRAQ proteomic analysis in the retinas collected from control and lens-induced myopic (LIM) mouse eyes treated with atropine. The myopic group received a (−15D) spectacle lens over the right eye on postnatal day 10 with or without atropine eye drops starting on postnatal day 24. Axial length was measured by op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 64 publications
6
53
0
9
Order By: Relevance
“…Atropine‐treated myopic retina has been associated with a significant reduction in the levels of GAT‐1 protein, suggesting the involvement of GABAergic mechanisms in the pathogenesis of myopia in neural retina (Barathi et al. ). Unfortunately, drug distribution to the posterior eye segment has always been a major challenge after topical administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atropine‐treated myopic retina has been associated with a significant reduction in the levels of GAT‐1 protein, suggesting the involvement of GABAergic mechanisms in the pathogenesis of myopia in neural retina (Barathi et al. ). Unfortunately, drug distribution to the posterior eye segment has always been a major challenge after topical administration.…”
Section: Discussionmentioning
confidence: 99%
“…A proteomic analysis of mouse retina revealed an up‐regulation of GAT‐1 in myopic retina, which decreased significantly following atropine therapy, highlighting the anti‐myopic role of the retina through atropine's interactions with the GABAergic signalling pathway (Barathi et al. ). However, topical drug delivery to the posterior segment, including the retina, has always been deemed challenging as very few drugs can maintain adequate concentrations in the posterior ocular tissues to exert its therapeutic action.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Concurrently, the role of visual experience in adapting ocular growth to suit the environment has been extensively investigated in animals where myopia can be induced by rearing with form deprivation occluders or negatively powered defocusing lenses. 19 Transcriptome and proteomics studies of ocular expression profiles in these animal models have associated thousands of genes [20][21][22][23][24][25][26][27][28] and hundreds of proteins [29][30][31][32][33][34][35][36][37] with environmentally driven growth. Enrichment analyses have aided interpretation of the wealth of data generated by exploratory human and animal studies 20,38 ; however, the key pathways by which genes and environment control ocular growth remain largely unclear.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that the retina is the major site that receives signals and determines the extent of eyeball elongation (195,196). Thus far, proteomic research has revealed a number of candidate proteins that may be associated with myopic eye growth (197)(198)(199). However, none of these studies have specifically focused on PTMs.…”
Section: Maldi-time Of Flight (Tof)/ms and Micro-lc/lc-ms/msmentioning
confidence: 99%